Sialendoscopy plus laser lithotripsy in sialolithiasis of the submandibular gland in 64 patients: A simple and safe procedure. Issue 5 (October 2019) - Guenzel, Thomas; Hoch, Stephan; Heinze, Niels; Wilhelm, Thomas; Gueldner, Christian; Franzen, Achim; Coordes, Annekathrin; Lieder, Anja; Wiegand, Susanne
Abstract: Objective: To demonstrate the safety and efficiency of holmium laser-assisted lithotripsy during sialendoscopy of the submandibular gland using a retrospective, interventional consecutive case series. Methods: We performed 374 sialendoscopies between 2008 and 2015 and evaluated all patients regarding clinical symptoms, clinical findings, therapy and outcome. We performed 109 procedures of holmium laser-assisted lithotripsy in 64 patients whose sialoliths measured 5 mm or more in diameter. In addition to retrospective case note reviews, we performed telephone interviews of all patients in January 2017. Results: We performed 374 consecutive submandibular gland sialendoscopy procedures in 276 patients between 2008 to 2015. Sialolithiasis had either previously been diagnosed, or symptoms highly suggestive of sialolithiasis of the submandibular gland presented in 197 patients. Holmium laser-assisted Laser lithotripsy was performed in 109 cases (64.9%). Smaller mobile concrement was removed directly either by forceps or wire basket, or following marsupialisation of the submandibular duct. This was the case in 88 patients (29.1%). Three patients (0.8%) required surgical removal of the submandibular gland due to early abscess. The majority of patients (n = 374 procedures; 90.1%) remained symptom-free after two or more years following intervention. In the remaining procedures (n = 37 procedures; 9.9%), patients reported discreet postprandial problems but did not seek medical attention. In total, we managed to preserve the submandibular gland and avoid open surgery in 99% of patients through endoscopic management of submandibular concrement and duct stenosis. Conclusion: Holmium laser-assisted lithotripsy is a simple, safe, and effective procedure for treating patients with sialolithiasis of the submandibular gland. Removal of the gland is rarely required, and removing the gland without prior sialendoscopy is no longer recommended. It should be offered to all patients with submandibular gland sialolithiasis, or such patients should be referred to the appropriate centre for sialendoscopy before submandibulectomy is considered.